Selective harmonic elimination in direct torque controlled permanent magnet synchronous motor drive. Issue 1 (7th January 2019) - Asadzadeh, Vahid; Dastfan, Ali; Darabi, Ahmad
Abstract : Purpose: The purpose of this paper is to describe a new method for selective harmonic elimination in a two-level three-phase inverter-fed direct torque controlled (DTC) permanent magnet synchronous motor (PMSM) drive to suppress unwanted resonant frequencies. Design/methodology/approach: The design methodology is based on random space vector pulse-width modulation (RSVPWM) of PMSM drives. MATLAB simulations support the validity of suggested structure. Findings: The simulation results of the proposed algorithm exhibit the development of a proper gap at the selected frequency in the frequency spectra of the motor input currents and voltages as well as lowering the ripples in the PMSM electromagnetic torque, stator current and flux linkage responses in compared with traditional DTC. Originality/value: The proposed algorithm is a revised form of the RSVPWM technique used in a closed-loop structure along with a sliding mode speed controller which is capable to deal with nonlinear motor loads in an online manner. This study can be beneficial for the designers of AC motor drive system who attempt to find a modulation method that can create a selective gap in the power spectrum density of the motor input voltages and currents, therefore, promote an acoustically pleasant drive or alleviate unwanted motor vibrations.